Ca(v)3.2 T-Type Ca2+ Channel-Dependent Activation of ERK in Paraventricular Thalamus Modulates Acid-Induced Chronic Muscle Pain - Chen, Wen-Kwei; Liu, Ingrid Y.; Chang, Ya-Ting; Chen, Yong-Cyuan; Chen, Chih-Cheng; Yen, Chen-Tung; Shin, Hee-Sup; Chen, Chien-Chang (SOC NEUROSCIENCE, 2010)
Treatments for chronic musculoskeletal pain, such as lower back pain, fibromyalgia, and myofascial pain syndrome, remain inadequate because of our poor understanding of the mechanisms that underlie these conditions. Although T-type Ca2+ channels (T-channels) have been implicated in peripheral and central pain sensory pathways, their role in chronic musculoskeletal pain is still unclear. Here, we show that acid-induced chronic mechanical hyperalgesia develops in Ca(v)3.1-deficient and wild-type but not in Ca(v)3.2-deficient male and female mice. We also show that T-channels are required for the initiation, but not maintenance, of acid-induced chronic muscle pain. Blocking T-channels using ethosuximide prevented chronic mechanical hyperalgesia in wild-type mice when administered intraperitoneally or intracerebroventricularly, but not intramuscularly or intrathecally. Furthermore, we found an acid-induced, Ca(v)3.2 T-channel-dependent activation of ERK (extracellular signal-regulated kinase) in the anterior nucleus of paraventricular thalamus (PVA), and prevention of the ERK activation abolished the chronic mechanical hyperalgesia. Our findings suggest that Ca(v)3.2 T-channel-dependent activation of ERK in PVA is required for the development of acid-induced chronic mechanical hyperalgesia.
Keywords: CALCIUM-CHANNELS; SYNAPTIC PLASTICITY; MECHANICAL HYPERALGESIA; COLORECTAL DISTENSION; NEUROPATHIC PAIN; SENSORY NEURONS; BRAIN-STEM; RAT; MICE; NUCLEUS